2016
DOI: 10.1089/jpm.2016.0133
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Cost for Patients Dying in the Intensive Care Unit and Implications for Cost Savings of Palliative Care Interventions

Abstract: Background: Terminal intensive care unit (ICU) stays represent an important target to increase value of care. Objective: To characterize patterns of daily costs of ICU care at the end of life and, based on these patterns, examine the role for palliative care interventions in enhancing value. Design: Secondary analysis of an intervention study to improve quality of care for critically ill patients. Setting/Patients: 572 patients who died in the ICU between 2003 and 2005 at a Level-1 trauma center. Methods: Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Finally, the authors of this study were able to demonstrate that a palliative management protocol, which is well known to improve the quality of care in the ICU, including reducing costs and mortality [25][26][27], should be sought and propagated, and this study proved that this strategy is underutilised, at least in the ICUs studied.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Finally, the authors of this study were able to demonstrate that a palliative management protocol, which is well known to improve the quality of care in the ICU, including reducing costs and mortality [25][26][27], should be sought and propagated, and this study proved that this strategy is underutilised, at least in the ICUs studied.…”
Section: Discussionmentioning
confidence: 67%
“…cedures. Despite several studies suggesting intensity 'steps' of strategies and procedures to be withdrawn or avoided in end-of-life ICU patients, our study revealed a great heterogeneity in this approach, with the presence of several non-aggressive procedures that may have resulted in increased costs, patient discomfort, and family distress [12,25]. Although in most cases this happened in situations where the end-of-life limitation decision had not even been made by the team, there were cases in which such procedures continued to be performed even in patients with defined (by the ICU team) "exclusive palliative care".…”
Section: Discussionmentioning
confidence: 81%
“…First, it should be noted that brain-dead nondonors do not require intensive care unit (ICU) occupancy after initial medical stabilization of the acute phase of their brain injuries (Shewmon 1998 ; Muramoto 2016 ). Their average daily cost of ICU care is estimated at 5000 US dollars per patient (Khandelwal et al 2016 ). Second, the long-term medical care of brain-dead nondonors with mechanical ventilation (through a tracheostomy) and enteral nutrition (through a gastrostomy) does not require ICU occupancy (Brown 2017 ).…”
Section: Legislative Enforcement Of Brain Death Determination In Muslmentioning
confidence: 99%
“…Nearly 25% of deaths in the United States occur in ICUs. 1,2 The majority of deaths in the ICU reflect a transition from curative to comfort-focused care through a process of palliative ventilator withdrawal (PVW). 3 Numerous professional societies and patient groups have advocated for improved management of ventilated ICU patients transitioning to palliative care.…”
mentioning
confidence: 99%